Whole-Genome Analysis of Livestock-Associated Methicillin-Resistant Staphylococcus aureus Sequence Type 398 Strains Isolated From Patients With Bacteremia in China. (16th March 2020) - Chen, Hongbin; Yin, Yuyao; Li, Xiaohua; Li, Shuguang; Gao, Hua; Wang, Xiaojuan; Zhang, Yawei; Liu, Yudong; Wang, Hui
Abstract: Sequence type (ST) 398 is the most prevalent clone of livestock-associated methicillin-resistant Staphylococcus aureus (MRSA). To evaluate the molecular characteristics and phylogeny of Chinese ST398 isolates, 4 MRSA ST398 strains and 4 methicillin-susceptible S. aureus (MSSA) ST398 strains were collected from patients with bacteremia at 6 teaching hospitals in China between 1999 and 2016. Moreover, 689 ST398 genome sequences were downloaded from the GenBank database for comparison. The 4 MRSA ST398 strains were resistant to β-lactam antibiotics, and 2 strains were also resistant to erythromycin. Among the 4 MSSA ST398 strains, 2 strains displayed multidrug resistance (MDR) and were resistant to penicillin, erythromycin, tetracycline, and gentamicin. The accessory genome of MSSA ST398 was more diverse than that of MRSA ST398. All 4 MRSA ST398 strains carried type V staphylococcal cassette chromosome mec elements; however, MSSA ST398 carried more resistance genes than MRSA ST398. These 4 MRSA ST398 strains carried hemolysin, along with virulence genes associated with immune invasion and protease. Phylogenic analysis showed that the 4 MRSA ST398 strains clustered in 1 clade. The global ST398 phylogeny showed that ST398 was divided into an animal clade and a human clade, and the ST398 strains of this study clustered in the human clade. A small number of human strains were also present in the animal clade and vice versa, suggesting transmission of ST398 between animals and humans. In conclusion, livestock-associated MRSA ST398 has caused severe infections in Chinese hospitals, and it should therefore be paid more attention to and monitored.